Sleep Characteristics and Influencing Factors of Sleep Quality in Patients With Inflammatory Bowel Disease-Peripheral Arthritis - Zhang, Yin; Pi, Bin; Xu, Xianlin; Li, Ying; Chen, Xiangfan; Yang, Ningxi; Li, Xiaoyan (Frontiers in Medicine, 2020)
Background: Patients with inflammatory bowel disease arthritis（IBDA）often accompany by sleep problems, but few studies have used polysomnography to investigate the objective sleep characteristics of IBDA. Methods: Patients in IBDA group, inflammatory bowel disease (IBD) group, healthy control (HC) group were examined by polysomnography (PSG) and the sleep characteristics were compared. Then the influencing factors of sleep efficiency in IBDA patients were analyzed. Results:There were significant differences in sleep parameters among the three groups (P<0.0001). The total sleep time (TST), rapid-eye-movement sleep （REM）time, slow wave sleep (S3 + S4) and sleep efficiency (SE) in the IBDA group were significantly less than those in the HC group and IBD group (P < 0.05), while the number and time of wake after sleep onset (WASO) and sleep latency (SL) were significantly longer than those in the HC group and IBD group (P < 0.05). For the above indicators, there was significant difference between patients in IBD group and HC group (P < 0.05). Hormone use, nocturnal gastrointestinal symptoms, joint pain, depression and disease in active phase were the influencing factors of sleep efficiency in patients with IBDA. Conclusions: The sleep quality of patients with IBD was poor than the control group, and that of patients with IBDA was even worse. Therefore, sleep management should be included in IBD management.